The improvement of standard operating procedures (SOP) and the process of grading the fresh palm fruit (BTS) at Kilang Kelapa Sawit Risda Ulu Keratong - Md Noor, Muhammad Amirulhadi; Ahmad Khairuddin, Muhammad Adib; Hassan Fikri, Mohd Hafiz; Abd Rahim, Mohd Faidhul Erfan; Roslizan, Mohammad Fithri; Khairudin, Mohd Sacirbey; Mahmood, Salwa; Saleh, Aslinda; Talib, Norfazillah (Penerbit UTHM, 2020)
Industrial Engineering and Quality Management is a branch of engineering subject that giving people knowledge about management in the industry. An industrial visit had been done due to this subject needed. The purpose of the visit is to identify an improvement that needed for the industry to make it more efficient and produce a good quality product and also managing the employee behaviour while at work. Industrial Engineering works to eliminate waste of time, money, materials, person-hours, machine time, energy, and other resources that do not generate value[1]. Industrial engineering is concerned with the development, improvement, and implementation of an integrated system of people, money, knowledge, information, equipment, energy, materials, analysis and synthesis. From all of the topic concern in industrial engineering then should be applied to the industry. In the factory sometimes have a bit of issue that they not notice out so there the function of Industrial Engineering will work. So from the industrial visit, there are some improvements that can be made such as grading system and standard of procedure. The old grading system of oil palm was not accurate enough, thus causing an error and producing poor oil quality. As the oil has less their grade so it will reduce the income of the factory because the buyer of the oil doesn’t take the responsibility due to the less of oil quality.